Pogrom in Gujarat: Hindu Nationalism and Anti-Muslim Violence in India - Jasani, Rubina (A journal of church and state, 2014)
Pogrom in Gujarat: Hindu Nationalism and Anti-Muslim Violence in India is an original and unique contribution to the literature on the anthropology of violence. Ghassem-Fachandi's style of writing is lucid, and his arguments are based on an authoritative understanding of Gujarati society and culture (both rural and urban). Though the writer modestly states that his aim is merely “to account for and understand the social factors of an empirical event” (p. 26), he does much more.